From law enforcement to protection?: interactions between sex workers and police in a decriminalized street-based sex industry - Armstrong, Lynzi (The British journal of criminology, 2017)
Legislative approaches to the sex industry are hotly debated internationally and in recent years interest in decriminalization of sex work has been growing. However, activities relating to commercial sex remain criminalized in many parts of the world. Street-based sex work is most often criminalized and is often more aggressively policed than indoor work. This paper explores changes in the relationship between police and street sex workers in New Zealand since the decriminalization of sex work in 2003, from the perspective of sex workers, police and support agencies. This paper concludes that decriminalization enabled a dramatic shift in the approach to policing sex work and emphasizes the importance of these findings in the context of global debates on prostitution law reform.